2011
DOI: 10.1016/j.bbamcr.2011.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide depletes phosphatidylinositol-3-phosphate from endosomes in a p38 MAPK-dependent manner and perturbs endocytosis

Abstract: Phosphatidylinositol-3-phosphate (PI3P) is a lipid that is enriched specifically in early endosomes. Given that early endosomes containing PI3P act as a microdomain to recruit proteins that contain a PI3P-binding domain (FYVE domain), the equilibrium between the production and degradation of PI3P influences a variety of processes, including endocytosis and signal transduction via endosomes. In the study reported herein, we have developed a novel analytical method to quantify the amount of PI3P in endosomes by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 56 publications
2
21
0
Order By: Relevance
“…The results of the morphological and biochemical analysis of the WT and Db cells indicated that p38 MAPK was activated in Db cells, which resulted in a decrease in phosphatidylinositol-3-phosphate (PI3P) in endosomes. This finding was consistent with our previous report that hydrogen peroxide (H 2 O 2 ) treatment of HeLa cells decreased intracellular PI3P in a p38 MAPK-dependent manner [22]. We could reconstitute successfully the typical endocytic pathways in WT and Db cells, and identified several perturbations of endocytic pathways that occurred specifically under diabetic conditions.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of the morphological and biochemical analysis of the WT and Db cells indicated that p38 MAPK was activated in Db cells, which resulted in a decrease in phosphatidylinositol-3-phosphate (PI3P) in endosomes. This finding was consistent with our previous report that hydrogen peroxide (H 2 O 2 ) treatment of HeLa cells decreased intracellular PI3P in a p38 MAPK-dependent manner [22]. We could reconstitute successfully the typical endocytic pathways in WT and Db cells, and identified several perturbations of endocytic pathways that occurred specifically under diabetic conditions.…”
Section: Introductionsupporting
confidence: 91%
“…We found that > 0.2 µg/ml SLO was sufficient to permeabilize ∼90% of HeLa cells. Previously, we showed that the concentration of SLO required to give this level of permeabilization depended on the cell type [8], [13][16], [22], probably due to the differences in cholesterol content in the plasma membranes of different cells. Subsequent experiments were performed with 0.13 µg/ml SLO.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Is a keratinocyte TTR receptor involved in agTTR uptake and in mediating agTTR-dependent oxidative stress? How does such oxidative stress influence endocytic transport pathways of skin cells [40,41] ?…”
Section: Discussionmentioning
confidence: 99%
“…Phosphatidylinositol 3-phosphate (PI3P) is found predominantly on early endosomal membranes, as well as in the intraluminal vesicles of multivescular endosomes (Simonsen et al, 2001). In Hela cells treated with hydrogen peroxide, PI3P was found to be obliterated from endosomes resulting in the perturbations in endocytosis pathway (Kano et al, 2011). PI3P has been shown to regulate receptor sorting but not transport in endolysosomal pathway (Petiot et al, 2003).…”
Section: Lipid Changes Related To Amyloid β-Induced Ad Pathologymentioning
confidence: 99%